Utilizing Multi-Omics Analysis to Elucidate the Molecular Mechanisms of Oat Responses to Drought Stress - Xiaojing Chen; Jinghui Liu; Baoping Zhao; Junzhen Mi; Zhongshan Xu (Plants)
The oat is a crop and forage species with rich nutritional value, capable of adapting to various harsh growing environments, including dry and poor soils. It plays an important role in agricultural production and sustainable development. However, the molecular mechanisms underlying the responses of oat to drought stress remain unclear, warranting further research. In this study, we conducted a pot experiment with the drought-resistant cultivar JiaYan 2 (JIA2) and water-sensitive cultivar BaYou 9 (BA9) during the booting stage under three water gradient treatment conditions: 30% field capacity (severe stress), 45% field capacity (moderate stress), and 70% field capacity (normal water supply). After 7 days of stress, root samples were collected for transcriptome and proteome analyses. Transcriptome analysis revealed that under moderate stress, JIA2 upregulated 1086 differential genes and downregulated 2919 differential genes, while under severe stress, it upregulated 1792 differential genes and downregulated 4729 differential genes. Under moderate stress, BA9 exhibited an upregulation of 395 differential genes, a downregulation of 669, and an upregulation of 886 differential genes, and it exhibited 439 downregulations under severe stress. Under drought stress, most of the differentially expressed genes (DEGs) specific to JIA2 were downregulated, mainly involving redox reactions, carbohydrate metabolism, plant hormone signal regulation, and secondary metabolism. Proteomic analysis revealed that in JIA2, under moderate stress, 489 differential proteins were upregulated and 394 were downregulated, while 493 differential proteins were upregulated and 701 were downregulated under severe stress. In BA9, 590 and 397 differential proteins were upregulated under moderate stress, with 126 and 75 upregulated differential proteins under severe stress. Correlation analysis between transcriptomics and proteomics demonstrated that compared with no drought stress, four types of differentially expressed proteins (DEPs) were identified in the JIA2 differential gene–protein interaction network analysis under severe stress. These included 13 key cor DEGs and DEPs related to plant hormone signal transduction, biosynthesis of secondary metabolites, carbohydrate metabolism processes, and metabolic pathways. The consistency of gene and protein expression was validated using qRT-PCR, indicating their key roles in the strong drought resistance of JIA2.